Morbid Placental Adhesion –A Nightmare for Obstetricians - Begum, Kohinoor (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Abstract not available J Bangladesh Coll Phys Surg 2019; 37(1): 1-3